A novel modular shallow mounted bollard system design and finite element performance analysis in ensuring urban roadside safety - Apak, Mustafa Yurdabal; Ergun, Murat; Ozen, Halit; Buyuk, Murat; Yumrutas, Halil Ibrahim; Ozcanan, Sedat; Atahan, Ali Osman (SAGE PUBLICATIONS LTD, 2023)
The safety of risky roadside zones such as kids' playgrounds, schools, bus stops, petrol stations, critical roadside facilities, and pavements are becoming a significant worldwide problem. This study focused on the roadside safety of critical above-ground assets of natural gas grids due to its consequences such as fire, blast, traffic interruptions, service downtime, and consumer displeasure during the repair process. In this regard, a novel modular shallow mounted bollard system was designed considering the disadvantages of conventional bollard systems in the literature and the demands/needs of related institutions. Numerical simulations were carried out to analyze the structural and safety performance capabilities of the originally designed bollard system following PAS 68:2013 standard. In addition, FE models were created and incorporated with the verified vehicle models to simulate dynamic behaviors. LS-DYNA software analyzed the FE models. As a result of the simulations, the newly developed fixed bollard design can safely stop vehicles that weigh 18,000 kg max., except for the 30,000 kg N3 class vehicle, up to 50 km/h. The results revealed that proposed bollard designs successfully met the standard requirements for the vehicle types and speed that represent general urban traffic characteristics. Thus, the new fixed bollard design will contribute to roadside safety in metropolitan areas by protecting critical hazardous roadside facilities. In the next stage, the newly designed barrier system should be optimized to lighten the system and reduce the costs.
Keywords: Roadside safety; barrier; bollard design; anti-ram system; numerical model; finite element analysis; LS-DYNA; failure analysis; CRASH TEST SIMULATION; CONCRETE BARRIER; IMPACT; SEVERITY; MODEL; Engineering; Transportation